New hopes and promises in the treatment of ovarian cancer focusing on targeted treatment—a narrative review - Satora, Małgorzata; Kułak, Krzysztof; Zaremba, Bartłomiej; Grunwald, Arkadiusz; Świechowska-Starek, Paulina; Tarkowski, Rafał (Frontiers in Pharmacology, 2024)
Unfortunately, ovarian cancer is still diagnosed most often only in an advanced stage and is also the most lethal gynecological cancer. Another problem is the fact that treated patients have a high risk of disease recurrence. Moreover, ovarian cancer is very diverse in terms of molecular, histological features and mutations. Many patients may also develop platinum resistance, resulting in poor response to subsequent lines of treatment. To improve the prognosis of patients with ovarian cancer, it is expected to make better existing and implement new, promising treatment methods. Targeted therapies seem very promising. Currently, bevacizumab - a VEGF inhibitor and therapy with olaparib - a polyADP-ribose polymerase (PARP) inhibitor are approved. Other methods worth considering in the future include: folate receptor α, immune checkpoints or other immunotherapy methods. To improve the treatment of ovarian cancer, it is also important to ameliorate the determination of molecular features to describe and understand which group of patients will benefit most from a given treatment method. This is important because a larger group of patients treated for ovarian cancer can have a greater chance of surviving longer without recurrence.